Construction Project Management in The Construction of Bajuin Sub-District Hall, Tanah Laut District, South Kalimantan Province: A Strategic Review - Muhammad Sarif; Rooslan Edy Santosa; Diyan Lesmana (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2026)
The purpose of this study was to determine the strategy of strengthening project managers, consultants, supervisors on the success of construction projects on the implementation of construction in the construction of the Bajuin District Hall, Tanah Laut Regency, South Kalimantan, and to determine the strengths, weaknesses, opportunities, and threats factors in the successful implementation of the construction project. The research method used is descriptive qualitative, using SWOT data analysis. Data collection techniques are carried out by survey and interview methods to obtain data and information directly from the field related to the strengthening of project managers, consultants, supervisors on the success of construction projects in the implementation of construction in the construction of the Bajuin District Hall, Tanah Laut Regency. The results of this study are to be reference material and information for companies regarding the influence of project managers, planning consultants and supervisory consultants on the success of construction projects.